Giant Cranial Vault Frontal Haemangioma – A Case Report - B, Sharma B; S, Sharma; M, Sarin; S, Jilowa; J, Kaur (Indian Journal of Case Reports, 2016)
Cranial vault haemangiomas are benign vascular lesions having capillaries, venous and cavernous channels. Histopathologically, these are almost like soft tissue haemangiomas. These are slow growing tumors and very rarely bleed. Cranial vault is uncommon site for the occurrence as compared to the vertebral. Cross sectional imaging like Computerized Tomography (CT) and Magnetic Resonance Imaging (MRI) play an important role in delineation of the vault pathologies. We present a 38-years old male who presented with slow growing swelling over the frontal bone without any neurological symptoms. CT and MRI imaging clinched the diagnosis which was confirmed subsequently by histopathological examination.